Answer:
( - 1 , - 1 )
Option D is the correct option.
Explanation:
y = - 2x - 3 → Equation ( i )
y = 3x + 2 → Equation ( ii )
Using elimination method
y + 2x = - 3
y - 3x = 2
---------------------
5x = - 5
Divide both sides of the equation by 5
![(5x)/(5) = ( - 5)/(5)](https://img.qammunity.org/2021/formulas/mathematics/high-school/wph1iarxzzrrq7acgrcksaz49vg0dm1ket.png)
Calculate
![x = - 1](https://img.qammunity.org/2021/formulas/mathematics/middle-school/mrspf492ee4lmy4cahzglkubjq1h2j8h7h.png)
Again, Putting the value of x in equation ( ii ) in order t get the value of y
![y = 3x + 2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/92d5g4hfat57bzucypg13t2cwdkd0ohcep.png)
plug the value of x
![= 3 * ( - 1) + 2](https://img.qammunity.org/2021/formulas/mathematics/high-school/puipy06ghrlgut9r9t9qtrlaoj9ds4rfm6.png)
Any expression multiplied by ( - 1 ) equals it's opposite
![= - 3 + 2](https://img.qammunity.org/2021/formulas/mathematics/high-school/8uc2phc1nz9vyrt88x3z2g6q3ivdpb5njm.png)
Calculate
![= - 1](https://img.qammunity.org/2021/formulas/mathematics/college/7avwdyqw926oxh3mrfuy9vfu5a6d7tpvve.png)
Therefore, The possible solution of the system is the ordered pair ( x , y )
![(x \:, y \: ) = ( - 1 \:, - 1)](https://img.qammunity.org/2021/formulas/mathematics/high-school/9u4i6ivuflw4y10kq0b1mxcp2hb7w2w0yc.png)
-----------------------------------------------------------------------
Check if the given ordered pair is the solution of the system of equation
![- 1 = - 2 * ( - 1) - 3](https://img.qammunity.org/2021/formulas/mathematics/high-school/kqxthaj4fgm2uptq5mk2clhm359tehfjwm.png)
![- 1 = 3 * ( - 1) + 2](https://img.qammunity.org/2021/formulas/mathematics/high-school/7x5frw4kj0xvcj911h791jf2ogzj6hyd6f.png)
Simplify the equation
![- 1 = - 1](https://img.qammunity.org/2021/formulas/mathematics/high-school/vl34rbew10t5945jm5geqdlohk7il8asnz.png)
![- 1 = - 1](https://img.qammunity.org/2021/formulas/mathematics/high-school/vl34rbew10t5945jm5geqdlohk7il8asnz.png)
Since all the equalities are true, the ordered pair is the solution of the system.
( x , y ) = ( - 1 , - 1 )
Hope this helps..
Best regards!!